Community Size, Socialization, and the Work Needs of Professionals - Adler, Seymour; Aranya, Nissim; Amernic, Joel (Academy of Management Journal, 1981)
This study tested whether the community size of early socialization directly affects adult work needs among professionals. The size of the community in which early socialization occurred generally had no significant effects on adult work needs. These results are consistent with previous findings on nonprofessionals.